2017
DOI: 10.1017/s1368980017002683
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the South African population’s salt intake: spot urine v. 24 h urine

Abstract: Estimations of Na excretion by the three formulas should be used with caution when reporting on Na intake levels. More research is needed to validate and develop a specific formula for the South African context with its different population groups. The WHO's recommendation of using 24 h urine collection until more studies are carried out is still supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…However, other research has highlighted that collecting 24‐hour urine collections is burdensome to participants, so spot urine collections are increasingly being used as a convenient and affordable alternative for estimating population salt intake. However, while some studies have shown that spot urine samples can provide a reasonable estimate of population‐level salt intake, there is not sufficient evidence to show whether this can be replicated in all population groups . Therefore, there are recommended against using spot urine collections, which is why we limited this review to studies that had used 24‐hour urine samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, other research has highlighted that collecting 24‐hour urine collections is burdensome to participants, so spot urine collections are increasingly being used as a convenient and affordable alternative for estimating population salt intake. However, while some studies have shown that spot urine samples can provide a reasonable estimate of population‐level salt intake, there is not sufficient evidence to show whether this can be replicated in all population groups . Therefore, there are recommended against using spot urine collections, which is why we limited this review to studies that had used 24‐hour urine samples.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the use of inadequate sodium intake assessment in observational studies is problematic. Six studies used spot urine collections to estimate usual sodium intake, despite the large body of literature showing that spot urine collections lack precision and accuracy for assessment of usual sodium intake in individuals . The risk of misclassification is high in these studies as demonstrated by Bland‐Altman analyses consistently showing poor agreement between measures of spot and 24‐hour urinary excretion for individuals .…”
Section: Discussionmentioning
confidence: 99%
“…Several formulae used to estimate 24‐hour urine sodium from spot collections have relatively small systematic errors in estimating average population sodium intake; however, some formulae used in different settings result in more substantive systematic error (>400 mg sodium) . Currently, all commonly used formulae systematically overestimate sodium intake at lower 24‐hour urine sodium and underestimate intake at higher 24‐hour urine sodium . Thus, changes in dietary sodium intake at the population level (both increases and decreases) will be systematically underestimated when assessed by spot urine samples.…”
Section: Use Of Spot Urine and Short Duration Timed Urine Collectionsmentioning
confidence: 99%
“…The TAG recommended to only consider using spot and short duration timed urine collections if there was a robust baseline calibration study with 24‐hour urine collections. The impact of the systematic error inherent in the use of spot urine collections in assessing changes in population averages over time, as planned in surveillance programs, remains to be established . A few studies have examined the average error of multiple spot or short‐term timed urine collections for assessing a population average sodium intake.…”
Section: Use Of Spot Urine and Short Duration Timed Urine Collectionsmentioning
confidence: 99%
See 1 more Smart Citation